PENGARUH KEBIJAKAN HUTANG, STRUKTUR MODAL, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Fahlevi, Abieta; Nazar, Mohamad Rafki (LPPM STIE Muhammadiah Bandung, 2023)
In this study, it has the objective of knowing the effect of debt policy. capital structure, and company growth on firm value. Company value, namely the company's description of the good or bad condition of the company in its performance carried out by company management, therefore it requires good connections between shareholders and management in order to optimize effective company value. This study used 40 companies with a unit sample of 200 primary consumer goods sectors listed on the IDX for 2017-2021 using the purposive sampling method. The analytical method used is statistical analysis and panel data regression analysis using eviews 12.0. The results of this study indicate that the debt policy, capital structure, and company growth have a significant effect on firm value simultaneously. Partially, debt policy and capital structure have no effect on firm value. Meanwhile, company growth has a significant positive effect on company value Keywords: Debt Policy, Capital Structure, Company Growth, Value Keywrods: Capital Structure, Company Growth, Debt Policy, Firm Value